Nouvelles perspectives sur les Cañaris d’hier et d’aujourd’hui : la céramique des Andes méridionales de l’Équateur de 100 av. J.-C. jusqu’à nos jours - Catherine Lara (Journal de la Société des Américanistes)
The Cañaris are a group currently settled in the southern Andes of Ecuador. They claim to be the descendants of the homonym group which—according to archaeological data—inhabited the same territory between at least 100 BC and the arrival of the Incas and Spaniards between the xv and xvi centuries AD. However, a recent ethnohistoric study claims that the vast majority of Precolumbian Cañaris did not survive these two successive conquests, and that the modern Cañaris are actually the result of a cultural mix between non local groups. This article seeks to test this hypothesis through the implementation of a technological approach applied to a comparative study of the ancient and current ceramics from the southern Andes of Ecuador. The results obtained also shed new light on the variability of Cañari Precolumbian ceramics.